2017
DOI: 10.1158/1538-7445.am2017-5125
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5125: Muscadine grape extract inhibits breast cancer brain metastatic cells by multiple mechanisms

Abstract: Tumor metastasis to the brain is a common complication of cancer, affecting 500,000 patients each year. Due to poor penetration of most chemotherapeutics into the brain, brain metastasis may occur even while systemic disease in under control. Despite aggressive treatments including radiation therapy, survival at 12 months following diagnosis is only 20%, underscoring the need for better means to prevent and/or treat brain metastases. Natural products have historically been a very successful sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Radiation therapy plays a pivotal role in cancer treatment, and efforts have been made to explore the combination of MGSE and radiation to amplify the effectiveness of radiation therapy ( Abshire & Lang, 2018 ). A study by Chen et al reported the effects of Muscadine grape extract on inhibiting brain metastasis in breast cancer cells ( Chen et al, 2017 ). The study also assessed the effectiveness of co-administering MGE and ionizing radiation (IR) in terms of therapeutic response.…”
Section: Combinatorial Approaches To Conventional Treatmentsmentioning
confidence: 99%
“…Radiation therapy plays a pivotal role in cancer treatment, and efforts have been made to explore the combination of MGSE and radiation to amplify the effectiveness of radiation therapy ( Abshire & Lang, 2018 ). A study by Chen et al reported the effects of Muscadine grape extract on inhibiting brain metastasis in breast cancer cells ( Chen et al, 2017 ). The study also assessed the effectiveness of co-administering MGE and ionizing radiation (IR) in terms of therapeutic response.…”
Section: Combinatorial Approaches To Conventional Treatmentsmentioning
confidence: 99%
“…Polyphenols are well recognized as one of the most important groups of natural antioxidants and chemopreventive agents [Scalbert et al, 2005]. They also have beneficial effects on human health due to their anti-inflammatory, immunomodulatory [Greenspan et al, 2005], anticancerogenic [Chen et al, 2017;Oyenihi Smith, 2019], antiviral [Nassiri-Asl and Hosseinzadeh 2016], and antioxidant properties [Zhang and Tsao, 2016]. Polyphenols are able to reduce the skin damage caused by solar radiations acting on keratinocytes [Nichols and Katiyar, 2010;Svobodovà et al, 2010].…”
Section: Introductionmentioning
confidence: 99%